Academic Services in Islamic Education Management Study Program: The Actualization of the Basic Values of the State Civil Apparatus at IAIN Palopo - Burhan Rifuddin; Dodi Ilham; Nurdin K (International Journal of Asian Education, 2020)
This research aims to develop the MPI study program 's academic information to improve the efficiency and effectiveness of education services by web-based information systems by updating the State Civil Establishment (ASN) values, using the approach of Participatory Action Research (PAR). The solution to the issue of web-based academic services in IAIN Palopo 's Islamic Education Management Study Programme, namely 1) conducting consultations related to web design of the Islamic Education Management Study Programme; 2) registering the web sub - domain and collecting materials that will be the content of the Islamic Education Management Study Program web.; 3) Installing web-based machines in registered sub-domains and creating a web-based framework for the Islamic Education Management Study Program; 4) designing a web-based display of the Islamic Education Management Study Program; 5) making menus and filling each menu with types of services, information, and activities related to the Islamic Education Management Study Program; 6) Implementation of web management training for prospective web administrators of Islamic Education Management Study Program; 7) Automation of web services published in the Islamic Education Management Study Program.